Identifikasi formalin dan boraks pada produk pangan di pasar tradisional kota Mataram - Fajriani, Laksmi Nur; Anisah, Anisah; Isasih, Widani Darma (Jurnal Agrotek Ummat, 2025)
Food Additives (BTP) are materials that are not usually used as food, have no nutritional value, and are intentionally added to food. The addition of several types of BTP to food is known to improve the quality of food products. However, at this time the use of prohibited BTP is still quite high, such as formalin and borax. Based on this, a study was conducted to identify the presence of formalin and borax content in several food products in traditional markets in Mataram city. This research method is qualitative descriptive with a sample size of four consisting of two samples for the formalin test and two samples for the borax test. The formalin test used wet noodle and tuna fish samples, while the borax test used meatball and lontong samples. Analysis of formalin and borax content was carried out using formalin reagents and borax reagents. The results of the study showed that the wet noodle and tuna fish samples were positive for formalin, while the meatball and lontong samples were not detected to contain borax.